Rich dad, poor dad : what the rich teach their kids about money-- that the poor and middle class do not! - Kiyosaki, Robert T., 1947- (New York : Plata Publishing, 2011)
Argues that a good education and a secure job are not guarantees for financial success, and describes six guidelines for making money work for you.
Keywords: Finance, Personal; Investments; Rich people